Wise parrot - Bond, Ruskin (New Delhi Rupa Publications, 2017)
Once upon a time, there was a Raja who owned a parrot and its name was Hiramantota.Delving into stories from folklore, epics and legends, Ruskin Bond brings to life a cast of fantastic and extraordinary characters. From the wise parrot Hiramantota who brings the fruit of immortality to the king but suffers grievously for it, to the Green Man of Sinai, who now haunts the desert of Sinai; from the boy wonder Jivaka who can solve all sorts of problems, to Sindbad the sailor, who has magical adventures on his voyages, these stories are as exciting as they are unforgettable.Retold here by Ruskin Bond with his characteristic wit, The Wise Parrot is a treasure trove of tales that is sure to delight and entertain a new generation of readers.
Keywords: Fiction